Toward high quality development in the People Republic of China. - Gang, Fan (Metro Manila, Philippines Asian Development Bank, 2019)
Advancing institutional reform, practicing the new development philosophy, and changing the approach to how five-year plans are drawn up will be vital for the People Republic of China. For the countrys five year plans, the paper proposes a new top down approach in which government departments and regional authorities contribute to national goals rather than the current practice of framing national master plans in terms of the individual goals of these entities.
Keywords: Economics; Industry and state; Electronic books